Network governance in low-carbon energy transitions in European cities: A comparative analysis. (March 2020) - Nochta, Timea; Skelcher, Chris
Abstract: This article evaluates the opportunities and limitations of network governance to support low-carbon energy transitions in European cities. Network visualization and statistical measures of network structure are combined with qualitative case study data to provide a comparative analysis of energy transition networks in Birmingham, Budapest and Frankfurt. Data reveal that existing networks differ in extent, integration and distribution of authority. Contextual characteristics help explain these differences, highlighting the importance of path dependencies and disjunctions in each city. These findings represent important considerations for the Transition Management model which aims specifically at governing sustainability transitions via network governance. Responding to a gap in the literature we demonstrate that Transition Management must be considered as an intervention into locationally specific settings and existing networks. The design of network structures and processes, as well as role of any 'transition manager', must reflect contextual factors and existing network considerations. Failure to account for contextual differences limits the model's capacity to contribute to sustainable energy transitions in different cities. Highlights: Transition Management promotes network governance to facilitate energy transitions. Contextual factors influence the form, extent and capacity of governance networks. TM must be considered as an intervention into locationally specific settings. Context, networks and diversity are key to the application of TM in cities.